Review of Communications Received Relating to General Assembly Matters (Ref 1 - 29). A/INF/73, Eleventh Session - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Appeals from different groups, parties and associations to the UN asking for: the United Nations to act on the question of Hungary; Withdrawal of Soviet troops from Hungary; Sending observers to Hungary; Support for Hungarian relief; Stopping the deportation of Hungarian citizens.